Doing it the ‘ASEAN Way’: a political perspective on creating a single currency in ASEAN - Ahmad, Edieusdi (2017)
ASEAN conduct itself through an approach called the ASEAN Way, a doctrine of non-interference policy. Due to the changing global geopolitical landscape, ASEAN needs to understand the feasibility of a single currency community in adapting to the highly volatile environment. The success of a single currency ASEAN lies within the political will of the ASEAN member states and the narrowing of socio-economic disparities among them. Alternative methods of strengthening the currencies include currency swapability or currency peg to an ASEAN+3 currency. Currency union is the last financial integration operatives that would sum up the AEC. ASEAN slow consensus building process, coupled with the EU lessons might ensure the thorough analysis of a currency union. Even if ASEAN does not achieve a single currency status, it will likely formulate sound monetary and financial policies for the region. This ensures stability for the years to come.